2014
DOI: 10.1002/app.41052
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, mechanical, and crystallization properties of ethylene‐tetrafluoroethylene copolymer/multiwalled carbon nanotube composites

Abstract: Multiwalled carbon nanotubes (MWCNTs) were melt‐mixed in a conical twin‐screw extruder with a random copolymer of ethylene and tetrafluoroethylene. Surprisingly, the electrical percolation threshold of the resultant composites was quite low; ∼0.9 wt %. In fact, this value is as low or lower than the value for most MWCNT/semicrystalline polymer composites made with roughly equivalent aspect ratio tubes mixed in a similar manner, for example, melt mixing. This low percolation threshold, suggestive of good disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Due to their excellent mechanical properties as well as high electrical and thermal conductivities, carbon nanotubes (CNTs) have been widely investigated in the field of material science and engineering . For polymer blends, CNTs have been widely studied with respect to their location in the blends as well as their effect on the domain size and shape .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent mechanical properties as well as high electrical and thermal conductivities, carbon nanotubes (CNTs) have been widely investigated in the field of material science and engineering . For polymer blends, CNTs have been widely studied with respect to their location in the blends as well as their effect on the domain size and shape .…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization behavior of random copolymer nanocomposites is also an interesting research topic. Similar to homopolymer nanocomposites, the addition of nanofillers in random copolymers can also promote the crystallization process and accelerate the crystallization rate 107–109 . For example, Verma and Choudhary 107 investigated the crystallization process of PP random copolymers under isothermal conditions in presence of multiwalled carbon nanotubes (MWCNT), and found that MWNT lowers the nucleation barrier, thereby accelerating the crystallization process.…”
Section: Simulations Of Nanofiller‐induced Copolymer Crystallizationmentioning
confidence: 99%
“…Similar to homopolymer nanocomposites, the addition of nanofillers in random copolymers can also promote the crystallization process and accelerate the crystallization rate. [107][108][109] For example, Verma and Choudhary 107 investigated the crystallization process of PP random copolymers under isothermal conditions in presence of multiwalled carbon nanotubes (MWCNT), and found that MWNT lowers the nucleation barrier, thereby accelerating the crystallization process. In addition, for the random copolymer nanocomposite systems, the crystallization behavior and crystal morphology also depend on the content of non-crystallizable comonomers.…”
Section: Crystallization Behavior Of Random Copolymer Nanocompositesmentioning
confidence: 99%